COVID – 19 AND STOCK MARKET VOLATILITY IN NIGERIA - BELLO ADO; IBRAHIM YARO (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
After the discovery of corona virus, in Wuhan city of Hubei Province in central China in the late part of December, 2019, the disease spread like wildfire across almost all the continent of the world within a short period of time. Global financial markets and particularly the stock markets have experienced deep dive in the value and abnormal volatility. The objective of this research is to assess the impact of Covid-19 on the Nigerian Stock Market Volatility using daily time series data ranging from January, 2020 to December, 2022. The data used in this study are Secondary data that were sourced from the Nigerian Stock Exchange (NSE) website and the Central Bank of Nigeria (CBN) Website, the Nigeria Center for Disease Control (NCDC). Unit Root Test: The unit root test was conducted to check the stationarity of a data series. the Augmented Dickey Fuller (ADF) (1979) and Phillips-Perron (PP) (1988) tests were conducted for this purpose. ARCHLM Test was also conducted to find presence of ARCH effects in the model to be estimated. The Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) was applied. The result shows that the impact of covid19 on stock market volatility is positive and statistically significant. The study recommends that covid-19 vaccine should be given to people in order to stop the spread of the disease.